Top earners: Cross-country facts - Alejandro Badel; Moira Daly; Mark Huggett; Martin Nybom (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2017)
We provide a common set of life-cycle earnings statistics using administrative data from the United States, Canada, Denmark and Sweden. Three qualitative patterns are common across countries: (1) the earnings distribution above the median fans out with age, (2) the extreme right tail of the earnings distribution becomes thicker with age, and (3) the growth rate of earnings over the working lifetime is larger for groups with higher lifetime earnings. Models of top earners should account for these qualitative patterns and, importantly, for how they quantitatively differ across countries.
Keywords: D31; D91; H21; J31; 330; Earnings; inequality; top earners; top incomes